Price and Volume Reactions to Public Information Releases: An Experimental Approach Incorporating Traders' Subjective Beliefs* - GILLETTE, ANN B.; STEVENS, DOUGLAS E.; WATTS, SUSAN G.; WILLIAMS, ARLINGTON W. (Contemporary Accounting Research, 1999)
Abstract This paper examines how market prices, volume, and traders' dividend expectations respond to public information releases in laboratory markets for a long‐lived financial asset. The objective is to study deviations from the symmetric information risk‐neutral rational expectations (RE) benchmark, which predicts no trade in such settings. The results of a series of double‐auction and call markets are reported in which traders manage a portfolio of cash and asset shares over 15 rounds of trading. A public signal regarding the value of the liquidating dividend is released every third round, and traders' subjective expectations of the liquidating dividend are elicited each round as cash‐motivated forecasts. We find that, despite the public dividend signal, traders' dividend forecasts are heterogeneous. Forecasts and prices both underreact to the public signals, with prices under‐reacting more than forecasts. In general, price changes are not closely associated with public signals, and there is greater excess price volatility in double auctions than in call markets. Forty‐three percent of trades are inconsistent with the trader's forecasts, and inconsistent trades occur more frequently in the double‐auction markets. On average, approximately 10 percent of the outstanding shares are traded in each round, and trading volume is increasing in the mean absolute forecast revision and decreasing in the contemporaneous dispersion in forecasts. These results suggest that differential processing of the public signal and/or speculative trading for short‐term gain may help to explain why symmetric information RE predictions are often not supported in empirical and experimental settings. They also suggest that market reactions to public information releases may be influenced by market microstructure.